Optimizing Income for Vegetable Farming in Puubunga Village Baula District Kolaka Regency - Hunowu, Devita Pratiwi; Salam, Idrus; Hidrawati, Hidrawati (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
This study aims to determine whether the poly-culture of vegetables (mustard greens, spinach, and kale) in Puubunga village has achieved optimal resource use and how much income the farmers use of the resources in optimal conditions. This research was conducted from July to August 2020. Analysis of the data used in this research is the analysis of optimality using the analysis tool Linear Programming POM for Windows 3. Sensitivity analysis is carried out to determine the sensitivity interval between changes in resources without changing the optimal income. The results of the optimization analysis show that resource use is not optimal. The use of land, mustard seeds, urea fertilizer, medicines (Dursban and Gramoxone) and labor is not yet optimal or not fully utilized while their availability is excessive, so it needs to be added or subtracted from the existing supply. The use of spinach seed, kale seeds, and manure are scarce resources because in optimal conditions all supplies are used up. The total income of vegetable farming (mustard greens, spinach, and kale) obtained under optimal conditions is IDR 777.275 per growing season, which is greater than the actual total income of vegetable farming of IDR 672.814 per growing season.